The role of the cooperative learning in enhancing the social adaptation for high school students - From the point of view of teachers of physical and sports education - - ameur taha; yazid gellati (sports creativity, 2025)
1- Title of the study: “The role of the cooperative learning in enhancing the social adaptation for high school students” - From the point of view of teachers of physical and sports education - 2- General question of the study: Does the collaborative learning play a role in achieving a social adaptation to high school students? Under this general question, other partial questions are inserted as well, as follows: 1. Does the collaborative learning contribute in reinforcing the relationship between the student and his classmates? 2. Does the collaborative learning contribute in improving the relationship between the student and the teacher? 3- Hypotheses of the study: + The general hypothesis: The collaborative learning plays a role in enhancing a social adaptation to high school students. + Partial hypotheses: -The contribution of the method of collaborative learning in reinforcing the relationship between the student and his classmates. -The contribution of the method of collaborative learning in improving the relationship between the student and the teacher. 4- Objectives of the study: The objectives of this study aims at: 1. Identifying the contribution of the method of collaborative learning in reinforcing the relationship between the student and his classmates. 2. Identifying the contribution of the method of collaborative learning in improving the correlation between the student and the teacher.